Postoperative Hypoxemia Is Common and Persistent. (September 2015) - Sun, Zhuo; Sessler, Daniel I.; Dalton, Jarrod E.; Devereaux, PJ; Shahinyan, Aram; Naylor, Amanda J.; Hutcherson, Matthew T.; Finnegan, Patrick S.; Tandon, Vikas; Darvish-Kazem, Saeed; Chugh, Shaan; Alzayer, Hussain; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND: The incidence, severity, and duration of postoperative oxygen desaturation in the general surgical population are poorly characterized. We therefore used continuous pulse oximetry to quantify arterial oxygen saturation (SpO2) in a cross-section of patients having noncardiac surgery. METHODS: Oxygen saturation, blinded to clinicians, was recorded at 1-minute intervals in patients >45 years old for up to 48 hours after noncardiac surgery in 1250 patients from Cleveland Clinic Main Campus and 250 patients from the Juravinski Hospital. We determined (1) the cumulative minutes of raw minute-by-minute values below various hypoxemic thresholds; and (2) the contiguous duration of kernel-smoothed (sliding window) values below various hypoxemic thresholds. Finally, we compared our blinded continuous values with saturations recorded during routine nursing care. RESULTS: Eight hundred thirty-three patients had sufficient data for analyses. Twenty-one percent had ≥10 min/h with raw SpO2 values <90% averaged over the entire recording duration; 8% averaged ≥20 min/h <90%; and 8% averaged ≥5 min/h <85%. Prolonged hypoxemic episodes were common, with 37% of patients having at least 1 (smoothed) SpO2 <90% for an hour or more; 11% experienced at least 1 episode lasting ≥6 hours; and 3% had saturations <80% for at least 30 minutes. Clinical hypoxemia, according to nursing records, measured only in Cleveland Clinic patients (n = 594), occurred in 5% of the monitored patients. The nurses missed 90% of smoothed hypoxemic episodes in which saturation was <90% for at least one hour. CONCLUSIONS: Hypoxemia was common and prolonged in hospitalized patients recovering from noncardiac surgery. The SpO2 values recorded in medical records seriously underestimated the severity of postoperative hypoxemia.